EVOLUTION OF DOMESTIC SMALL AND MEDIUM ENTERPRISES: HISTORICAL JOURNEY - Khamatkhanova, M.A. (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the features of the formation of small and medium enterprises in the Russian Federation, outlines the stages of development of small and medium enterprises in the 1990s. The place of small and medium enterprises in the formation of the country's GDP is indicated.